2021
DOI: 10.1108/f-12-2020-0130
|View full text |Cite
|
Sign up to set email alerts
|

The mediation effects of finance on the relationship between service quality and performance of hospital facilities management services

Abstract: Purpose With rising health-care costs and the financial constraints in most developing countries, prioritization of needs have become an issue of strategic importance in public hospitals. As a result, there is the intense competition of scare resources between core health care and non-core facilities management (FM) services. Given that financial resources are needed to facilitate the smooth operation of the FM department, this paper aims to investigate the direct and indirect effects of finance on the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
(53 reference statements)
2
9
0
Order By: Relevance
“…This suggest that apart from the Assurance dimension, for the other dimensions, any increase in the FM service quality and adequacy of health-care resources will have a corresponding positive effect on patient’s health-care experience. This supports the assertion that quality in FM delivery in the management of health-care facilities needs continuous improvement in the management of all system and processes (Lai et al , 2022a; Amos et al , 2021b).…”
Section: Discussion Of Results and Implicationssupporting
confidence: 81%
See 2 more Smart Citations
“…This suggest that apart from the Assurance dimension, for the other dimensions, any increase in the FM service quality and adequacy of health-care resources will have a corresponding positive effect on patient’s health-care experience. This supports the assertion that quality in FM delivery in the management of health-care facilities needs continuous improvement in the management of all system and processes (Lai et al , 2022a; Amos et al , 2021b).…”
Section: Discussion Of Results and Implicationssupporting
confidence: 81%
“…According to Zhou et al (2017) and Demir (2022), customers develop more positive perceptions towards organisations they believe value and care about their customers and their feedback. Also, there is the need to standardise both core health care and FM service tasks to ensure smooth and prompt running of activities and processes (Amos et al , 2021b). This, according to Liu et al (2022) is particularly so for a health-care facility that needs to operate daily to ensure patient safety and maintain high standards of service quality.…”
Section: Discussion Of Results and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the service quality assessment in the property management industry found significant influence of empathy toward customer satisfaction [19]. These findings correspond to previous studies of positive relationship between empathy and households' satisfaction in the property management industry [55], building maintenance industry [56]. Empathy also contributes to the significant stimulus towards postpurchase satisfaction of home buyers [37].…”
Section: Empathysupporting
confidence: 84%
“…The SERVQUAL model pioneered by Parasuraman et al (1988) was found to be widely used in evaluating performance of service or service providers in different service sectors. For instance, in the facilities management field, SERVQUAL model, have been wholly or partly used to study issue of service quality and/or performance in different organisations such as hospital (Amos et al, 2020(Amos et al, , 2022, educational institutions (Aziz & Sapri, 2013;Ideris et al, 2016), commercial real estate (Karunasena et al, 2018) and hospitality (Al-Gasawneh et al, 2022;Günaydın, 2022) and host of others.…”
Section: Conceptual Frameworkmentioning
confidence: 99%